Pembrolizumab combined with lenvatinib and metronomic cyclophosphamide in platinum-resistant ovarian cancer: a case report of durable clinical response - Dai, Guanlin; Tang, Furong; Wang, Ping; Wang, Danqing (Frontiers in Oncology, 2025)
Most patients with ovarian cancer experience disease recurrence or progression, and ultimately progress to platinum resistance. Standard treatments for platinum-resistant ovarian cancer (PROC) include non-platinum chemotherapy, targeted agents, and immunotherapy. Despite recent advances in individualized management of PROC, median progression-free survival remains limited. Effective treatments are still lacking for PROC treatment. Given the current landscape of immunotherapy in ovarian cancer, research is ongoing to investigate immune modulators to counteract immune escape and enhance the efficacy of immune checkpoint inhibitors. Here, we reported a successful administration of a triple regimen comprising pembrolizumab, lenvatinib and metronomic cyclophosphamide, as the third-line treatment in a patient with PROC. This combination resulted in a durable response, with a PFS of 52 months as of the last follow up. This is the first report on this triple regimen in PROC and its promising outcome suggested that this regimen deserves further investigation as a potential therapeutic option for PROC.